Analisa Filter Pasif pada Static Var Compensator (SVC) Mereduksi Total Harmonic Distortion (THD) di Sistem Transmisi Bali.: Analysis of Passive Filter on Static Var Compensator (SVC) to Reduce Total Harmonic Distortion (THD) in Bali Transmission System - Made Dika Nugraha; Kadek Agus M.D.P; I Nyoman A. Prabawa (Jurnal Teknik Elektro dan Komputer, 2023)
Abstract — SVC functions as a voltage profile regulator, harmonic reduction and voltage stabilizer for transmission in the province of Bali which serves 15 substations, while using nonlinear loads so that harmonics are formed on the current and voltage graphs which result in voltage drops in the transmission network. So, it is necessary to dampen the voltage harmonics or Total Harmonic Distortion (THD) with Passive Filters. The method used is the transmission system simulation in PSCAD software with the IEEE 14-bus standard. The percentage value results in the order before and after installing the Passive Filter on the SVC are in accordance with IEEE Standard 519-2014 (max 2.5% for THDv) namely the 3rd order, namely 1.99% to 1.95%, the 5th order, namely 3, 40% to 2.13%, 7th order namely 2.81% to 2.06%, 9th order namely 1.67 to 1.64%, 11th order 2.09% to 1.84%, 11th order 13th order, namely 2.11% to 1.98% and 15th order, namely 2.19% to 1.96%.   Key words— Passive Filter; Static Var Compensator; Total Harmonic Distortion   Abstrak — SVC berfungsi sebagai pengatur profil tegangan, penurunan harmonisa dan penstabil tegangan pada transmisi di provinsi Bali yang melayani 15 gardu induk, sedangkan dengan penggunaan beban nonlinier sehingga terbentuk harmonisa pada grafik arus maupun tegangan yang berakibat terjadinya jatuh tegangan pada jaringan transmisi. Sehingga diperlukan peredaman pada harmonisa tegangan atau Total Harmonic Distortion (THD) dengan Filter Pasif. Metode yang digunakan yaitu simulasi sistem transmisi dalam software PSCAD dengan standart IEEE 14-bus. Hasil nilai persenan pada orde sebelum dan sesudah pemasangan Passive Filter pada SVC sesuai dengan Standar IEEE 519-2014 (max 2,5% untuk THDv) yaitu orde ke 3 yaitu 1,99% menjadi 1,95%, orde ke 5 yaitu 3,40% menjadi 2,13%, orde ke 7 yaitu 2,81% menjadi 2,06%, orde ke 9 yaitu 1,67 menjadi 1,64%, orde ke 11 2,09% menjadi 1,84%, orde ke 13 yaitu 2,11% menjadi 1,98% dan orde ke 15 yaitu 2,19% menjadi 1,96%.   Kata kunci — Filter Pasif; Static Var Compensator; Total Harmonic Distortion